COMPARATIVE ANALYSIS OF DETECTIVE WORK REGULATION IN LATVIA AND LITHUANIA - Rimanas, Oļegs (Administrative and Criminal Justice, 2016)
The article analyses the detective work regulation specifies in Latvia and Lithuania. It can be concluded that law clearly states which actions conform with detective work and that information collected within detective work – are recognized as legally significant . According to regulation – detective activities cannot be recognized as unlawful interference in person's private life, thereby ensuring personal privacy. Since Lithuanian law has been adopted recently – it is more in line with current situation and conditions.